Urban governance and sustainability barriers in Indonesia: Tracking the forward policy design - Nicolaus Petrus Likuwatan Werang; Maria Lusiana Florentin Werang; Rizky Amalia Putri (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Indonesia’s urban governance and sustainability reveal a significant barrier to the concretization in the field. Interestingly, while the government has invented a bunch of initiatives to assist the goals, their insignificant progress has been consistently revealed. Methods: Our study employed a systematic literature review (SLR) to track the issue comprehensively and carefully to estimate the objectivity, accuracy, relevance, linked to the research theme and it was assisted by Publish or Perish (PoP) software to collect, organize, comprehend, and scrutinize the data based on scientific papers pertinent to the research theme. Findings: Our findings display the significant barriers (e.g., fragmented governance, weak concretisation systems, and underdeveloped institutional mechanisms that block urban governance and sustainability in Indonesia. To swamp, we offer the forward policy design with three leading actions (i.e., integrated policy framework, capacity building, fiscal and legal reform). Conclusion: Based on these, we believe the issues of urban governance and sustainability barriers will get back on track and achieve the goals consistently. Novelty/Originality of this article: Our novelty contributes to a comprehensive framework that bridges the concepts of spatial planning, governance structures, and sustainability objectives in Indonesian urban areas in an inclusive, equitable, and resilient context.